Determinants of ethical identity disclosure in Islamic banks: an analysis of practices in Bahrain and Malaysia - Rashidah Abdul Rahman,; Nur Syatilla Saimi,; Danbatta, Bello Lawal (Penerbit Universiti Kebangsaan Malaysia, 2016)
Islamic banks are banks that are set up to operate within the Islamic business framework that is more equitable and based on socio-economic welfare of the society and the people. In Islamic law on commercial transactions and other related contractual activities (the framework), transparency and adequate disclosure are the fundamental determinants of a successful and peaceful relationship between the contracting parties. This is because the stakeholders of Islamic banks believed that the prescriptions of the framework would be the key determinants of the bank’s Ethical Identity Disclosures (EID). This study aimed at exploring and identifying the practical determinants of EID in Islamic banks. Disclosure information in annual reports (from 2007 to 2011) of 21 Islamic banks operating in Bahrain and Malaysia was gathered and analysed using Ethical Identity Index (EII) and Multiple Regression Analysis (MRA) models. The results of EII and MRA on nine ethical disclosure dimensions consisting of 80 constructs and 4 assumed determinants of EID among Islamic banks indicated that EID of both countries is low and that independent directors do not affect the level of social disclosure. However, board size, Shari’ah supervisory Board and investment account holders can significantly influence the disclosure level in Islamic banks. Hence, we conclude that our findings are in conflict with main theories such as agency theory, however supports institutional theory.